Charge transfer accelerating strategy for improving sensitivity of droplet based triboelectric sensors via heterogeneous wettability. (15th June 2022) - Jang, Sunmin; Joung, Yoonsu; Kim, Hyeonsu; Cho, Sumin; Ra, Yoonsang; Kim, Minchang; Ahn, Dahoon; Lin, Zong-Hong; Choi, Dongwhi
Abstract: The triboelectric platform (TEP) generates electric signals, such as current with the sequential contact and detachment between two different material surfaces. Among the various practical application of the TEP, the self-powered sensors based on the contact of liquid droplets on a solid surface is getting the spotlight as a key application of the Liquid-to-Solid interacting TEP (L-S TEP). In this study, the current signal amplification strategy, which accelerates the charge transfer in the droplet with the utilization of the spatially heterogeneous wettability (HeW) surface is proposed. The HeW surface can be facilely fabricated by physically depositing the porous cellulose membrane (PCM) on the hydrophobic contact layer. About 50 times larger current signal can be easily generated with the charge transferring channel widening effect. By utilizing HeW surface assisted L-S TEP (HeW-TEP) on the sensor module as a self-powered electrolyte concentration sensor and self-powered raindrop acidity sensor, the data perusal can be accomplished via wireless sensing system. Considering we first propose a novel current signal amplification strategy of the droplet based L-S TEP based on the acceleration of the charge transfer, which has not received much attention to date, this study would greatly contribute to enhancing its practicality. Graphical Abstract: ga1 Highlights: Proposal of signal amplifying strategy from the liquid-to-solid interacting triboelectric platform. Acceleration the charge transfer in the droplet with the adoption of the heterogeneous wettability surface. Adoption of the porous cellulose membrane to generate heterogeneous wettability surface. Suggestion of wireless sensor system which can peruse the electrolyte concentration and acidity information.